Demystified… recombinant antibodies. Issue 9 (27th August 2004) - Smith, K A; Nelson, P N; Warren, P; Astley, S J; Murray, P G; Greenman, J
Abstract : Recombinant antibodies are important tools for biomedical research and are increasingly being used as clinical diagnostic/therapeutic reagents. In this article, a background to humanised antibodies is given, together with details of the generation of antibody fragments—for example, single chain Fv fragments. Phage antibody fragments are fast becoming popular and can be generated by simple established methods of affinity enrichment from libraries derived from immune cells. Phage display methodology can also be used for the affinity enrichment of existing antibody fragments to provide a reagent with a higher affinity. Here, phage antibodies are demystified to provide a greater understanding of the potential of these reagents and to engage clinicians and biomedical scientists alike to think about potential applications in pathology and clinical settings.